Synthesis and interaction of secondary N-nitrosamines with acetylcholinesterase - Mmutle, Tsietso Bernard (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1991)
Secondary N-nitrosamines: diphenylnitrosamine (DPhNA), dimethylnitrosamine (DMNA), diethylnitrosamine (DENA), dipropylnitrosamine (DPNA), dibutylnitrosamine (DBNA), diethanolnitrosamine (DEtNA), methylnitrosoglycine (MNGly), nitrosopyrrolidine (NPyr), nitrosomorpholine (NMor) and nitrosopiperidine (NPip) were synthesised and their interaction with acetylcholinesterase (AChE) was investigated. Analyses of kinetic results show that DMNA (Ki=34.78 Î¼M); DENA (Ki=54.24 Î¼M); DPNA(Ki=60.36 Î¼M); DBNA(Ki=95.54 Î¼M); DEtNA(Ki=43.68 Î¼M)MNGly (Ki=30.18 Î¼M); NPip (Ki=123 Î¼M); NPyr (Ki=66.07 Î¼M), NMor (Ki=73.93 Î¼M) and DPhNA (Ki=20.32 Î¼M) are competitive and reversible inhibitors of acetylcholinesterase, with respect to the substrate, acetylthiocholine chloride, ATChCl. With time they act as irreversible covalent inhibitors with dipropy1nitrosamine producing 72% inactivation after 60 minutes. Scatchard analyses of f1uorometric titrations, (Kd=0.75mM-4.09mM); gel chromatography (Kd=O. 80mM-4. 60mM) and equilibrium dia1ysis (Kd=O. 71mM- 4.21mM) for MNG1y, DMNA, DEtNA, DENA, DPNA, NPyr, DSNA, NMor and NPip show that these compounds have weaker affinity for the enzyme, as compared to the much tightly binding aromatic DPhNA, Kd values (0.65mM, 0.68mM and 0.68mM) for fluorometric experiments, gel chromatography and equilibrium dialysis respectively. In all cases, the number of binding sites of acetylcholinesterase averaged to four.
Keywords: Chemistry, Physical and theoretical; Enzyme kinetics